Alfa Value Scalability on Single and Double Exponential Smoothing Comparatives - Yuli Astuti; Irma Rofni Wulandari; Muhammad Noor Arridho; Erni Seniwati; Dina Maulina (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
To find out sales forecasts in the future, it is not only based on estimates but must be calculated carefully based on the experience of previous sales transactions. This observation can be made based on sales data a few months ago to be used as actual data to get predictive value in the future period. Prediction or forecasting is done with two methods Single Exponential Smoothing (SES) and Double Exponential Smoothing (DES), from these two methods, will be sought the most suitable alpha value to get the percentage error value. There are two error values : Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). By using sales data from February to December 2019, the predicted value of 430 orders was obtained in the SES method and resulted in a sales prediction of 402 orders in the DES method with the smallest error accuracy value of 26.88% in the SES method and an accuracy value of 22.71%. in the DES method with the acquisition of scalability of the right alpha value for both, namely 0.3 and the beta value of 0.3 in the DES method